Controlled testing of novel portion control plate produces smaller self-selected portion sizes compared to regular dinner plate - Joel W. Hughes (BMC Obesity, 2017)
Abstract Background Obesity is a global health crisis, and portion control is a key method for reducing excess body weight. Given consumers’ familiarity with large portion sizes, reducing portion sizes can be difficult. Smaller plates are often recommended to reduce portion sizes and appear to reduce portion sizes. However, there are no studies evaluating dishes specifically designed to facilitate portion control. The aim of the present study was to validate the efficacy of a novel portion control plate inspired by the Ebbinghaus and Delboeuf visual illusions to promote serving smaller portions compared to a larger dinner plate. Methods In two studies with a total of 110 university students, we determined whether the use of the portion control plate would result in smaller food portions compared to a larger dinner plate. The portion control plate was smaller and incorporated portion size indicators. Study 1 used instructions from My Plate based on plate ratios (e.g., “the USDA recommends filling half your plate with vegetables”) and study 2 used absolute portion size recommendations (e.g., “1 cup of vegetables”). Results The portion control plate produced smaller self-selected servings in both studies. However, the servings of vegetables selected were smaller than recommended portion sizes for both the portion control plate and the regular dinner plate. Conclusions Portion control plates have the potential to reduce self-selected portion sizes. Future research should include studies in a broader range of ages and clinical trials of portion control dishes for weight loss.